Internal Factors Affecting Dividend Policy In Consumer Non Cyclical Industry - Joel Napoleon, Ivan; Pusvikasari, Nila (Media Bisnis, 2025)
This research is conducted to examine the influence of internal factors of company on Dividend Policy. The independent variables in this study are Firm Size, Profitability, Growth Opportunity, Financial Leverage, and Liquidity. Research object will focus on companies in the Consumer Non Cyclical industry listed in Indonesia Stock Exchange (IDX) that consistently paid dividends during the period 2012-2022. A total of 10 companies were selected as the research sample through purposive sampling. Data analysis was performed using multiple linear regression. Based on the analysis results, it can be concluded that Firm Size, and Financial Leverage do not have an effect on Dividend Policy, while Profitability, Growth Opportunity, and Liquidity have a negative effect on Dividend Policy.